Curso de Matemática licenciatura/UFSM: uma análise de projetos pedagógicos (2013-2019) - Oliveira, Rochele Ribas de (2022)
The objective of this master’s thesis is to understand the curricular structure of the UFSM undergraduate degree in Mathematics from interrelationships between pedagogical and disciplinary knowledge in the 2013 and 2019 Course Pedagogical Projects (CPPs). By means of a qualitative approach, this study is organized in the multipaper format, structured by three manuscripts that present as objectives, respectively: to outline stricto sensu research that deals with the analysis of pedagogical projects of initial training degree programs for mathematics teachers, considering as repositories the Brazilian Digital Library of Theses and Dissertations (BDTD) and the Directory of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES); to characterize the Licentiate degree in Mathematics/UFSM with emphasis on its objectives, graduate profile, teaching practice and research initiation, based on the provisions of the 2013 CPP and the 2019 CPP; to identify evidence of pedagogical knowledge in compulsory courses that make up the 2013 CPP and the 2019 CPP of the Licentiate degree in Mathematics/UFSM. Beyond the singularities, the manuscripts recognize the relevance of courses that deal with pedagogical knowledge in curricular proposals of undergraduate degrees that train mathematics teachers. Thus, we identified in BDTD and CAPES ten studies on initial teacher education that consider the analysis of pedagogical projects, of which four emphasize specific mathematics courses and subjects; three highlight academic internships, and three focus on knowledge and know-how. Among the considerations, we highlight the emphasis of disciplinary knowledge over pedagogical knowledge. In analyzing the trajectory of the Licentiate degree in Mathematics/UFSM, in particular, we observed six curricular reforms. Since the implementation of the Bachelor’s degree in Mathematics in 2001, the pedagogical projects of both degree programs started to share a significant amount of courses, maintaining a common core of two years until the 2005 PPC privileged disciplinary knowledge in the first half of the degree program. As of the 2013 CPP, and especially in the 2019 CPP, we can observe a new characterization for teacher education in the program, with greater articulation between pedagogical and disciplinary knowledge, which promoted significant changes in the degree program objectives and in the graduate profile. Among the changes proposed by the 2019 CPP, we categorized such courses into four movements: in the first one, we verified interruption of imbrications between Mathematics Didactics and Mathematics Education; in the second one, we observed expansions in the courses that deal with the use of technological resources, teaching materials, and methodological approaches; in the third one, we observed the insertion of new courses that have an emphasis on contemporary issues and on research in Mathematics Education; in the fourth one, we observed courses that were kept, but with reduced course load. The interrelations between pedagogical and disciplinary knowledge are privileged in courses in the areas of Mathematics Education, and less frequently in the area of Education, and the analysis of their syllabuses shows that they provide the opportunity for political, philosophical, social, and cultural reflections that cover different realities and contexts.